2022
DOI: 10.2478/kbo-2022-0052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Globalization on the Internationalization and Management of the Activity of the Multinational Companies

Abstract: Under the conditions of the contemporary economy, the intensification of foreign trade is a fundamental requirement of economic growth, of business internationalization and, implicitly, of economic globalization. On the other hand, business development in the international environment, regardless of the size of the economic entities or their field of activity, tends to become a prerequisite of organizational existence. For this reason, the business strategies must be synchronized with the requirements and dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Word documents can be subjected to several operations designed to protect the data contained against unauthorized access to them. Stanciu et al (2022) in their paper concluded that "In a dynamic and versatile economic environment, in order to be competitive, the companies must diversify and develop their activities". The activity means documents also, and that's why it's very important to protect them.…”
Section: Case Study: Protecting a Microsoft Word Documentmentioning
confidence: 99%
“…Word documents can be subjected to several operations designed to protect the data contained against unauthorized access to them. Stanciu et al (2022) in their paper concluded that "In a dynamic and versatile economic environment, in order to be competitive, the companies must diversify and develop their activities". The activity means documents also, and that's why it's very important to protect them.…”
Section: Case Study: Protecting a Microsoft Word Documentmentioning
confidence: 99%